La ciencia y la tecnología como tópicas de la publicidad gráfica en la prensa de 1922 en México - López León, Ricardo (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2010)
In this article I apply a sociosemiotic model to analyze press graphic advertising. The selected pieces refer to what I have identified as the «topic of science and technology». In this article I show the materials that this topic offered to design advertising in the year of 1922 in a Mexican newspaper called El Universal. So, the reader will identify two main objectives: the first is to see if a socio-semiotic model can be used to visual image analysis, and the second one, if there is such a thing as a «topic of science and technology» and how it works. As collateral, this paper is looking forward to contribute to the construction of Mexican advertising history. I have to mention that this is only a part of my doctoral thesis.
Keywords: Mexican advertising history; Science and technology; Sociosemiotics; Topics